Near-Infrared Properties of Hybridized Plasmonic Rectangular Split Nanorings - 廖中伟 黄映洲 王小勇 周洋洋 王蜀霞 温维佳 (Chinese physics letters, 2014)
The near-infrared properties of gold rectangular split nanorings （RSNs） are investigated by simulation using the finite element method. In the results, the distribution and enhancement of electromagnetic （EM） fields are confirmed by the distribution of charge and current density. The spectrum variation with split distance of RSNs in absorption is in accordance with the hybridization theory. The influence of split distance and light wavelength on the enhancement of EM field is also studied for devices that make use of surface plasmon resonance in nearinfrared, such as in optical trapping, biomedicine, and solar energy. Additionally, the spectra in mediums with various refractive indices suggest the potential application of the hybridized plasmonic RSNs as an ultra-sensitive sensor in the near-infrared region.